Physical Activity and Inhibition of ACE Additively Modulate ACE/ACE-2 Balance in Heart Failure in Mice - Tyrankiewicz, Urszula; Olkowicz, Mariola; Berkowicz, Piotr; Jablonska, Magdalena; Smolenski, Ryszard T.; Zoladz, Jerzy A.; Chlopicki, Stefan (Frontiers in Pharmacology, 2021)
Angiotensin-converting enzyme inhibition (ACE-I) and physical activity favourably modulate the ACE/ACE-2 balance. However, it is not clear whether physical activity and ACE-I could synergistically modulate ACE/ACE-2 balance in the course of heart failure (HF). Here, we studied the effects of combined spontaneous physical activity and ACE-I treatment on angiotensin (Ang) pattern and cardiac function in a mouse model of HF (Tgαq*44). Tgαq*44 mice with advanced HF (at the age of 12 months) were running spontaneously in a spinning wheel (exercise training group, ExT) and/or were treated with ACE inhibitor (ACE-I, perindopril, 10 mg/kg) for 2 months. Angiotensin profile was characterized by an LC-MS/MS-based method. The cardiac performance was assessed by in vivo MRI (BioSpec® 9.4 T, Bruker, Germany) under isoflurane anaesthesia (1.7%). Ang-(1-7)/Ang II ratio in both plasma and the aorta was significantly higher in the combined treatment group as compared to the ACE-I group or ExT alone, suggesting the additive favourable effects on ACE-2/Ang-(1–7) and ACE/Ang II axes’ balance induced by a combination of ACE-I with ExT. The basal cardiac performance did not differ among the experimental groups of Tgαq*44 mice. We demonstrated additive changes in ACE/ACE-2 balance in both plasma and the aorta by spontaneous physical activity and ACE-I treatment in Tgαq*44 mice. However, these changes did not result in an improvement of failing heart function, most likely because the disease was at the end stage. Ang-(1–7)/Ang II balance represents a valuable biochemical end-point for monitoring therapeutic intervention outcome in heart failure.